A comparative study of activitybased costing (abc) and time-driven activity-based costing (tdabc) on cost accounting - Nurul Farahin, Zamrud (2021)
In any business competition, it is important for the company to incorporate an accurate cost estimation to decide the best price for products to gain profits. By the 1980s, Traditional Cost Accounting (TCA) is no longer reflecting the current economic reality due to distorted information about the profitability of the company’s orders, products, and customers. In addition, Activity-based Costing (ABC) is a costing method originally developed to overcome the shortcoming of TCA method in the era of rapidly increasing product complexity and diversification. However, it is not universally accepted because it ignores the potential for unused capacity which will be beneficial for forecasting. Nevertheless, the current published work does not clearly state of capacity cost rate, practical capacity and time equation. The aim of this work is to compare the advantages of ABC and Time-driven Activity-based Costing (TDABC) by analyzing the features towards costing sustainment. The work begins by collecting data at electrical and electronic industry located at Pahang and the product selected is a magnetic inductor. ABC focuses on the costs inherent in the activity-based products to produce, distribute or support the products concerned. TDABC uses time equation and capacity cost rate to measure the unused capacity with respect to the time and cost. Through ABC method, this work successfully gathered the time allocated by operator to complete the task given. The largest time allocated by operator is at epoxy application activity which is 43.89% and the smallest is 0.63% at oven curing. The highest amount of cost of capacity is epoxy application activity with cost of MYR 1,665,729.98 and the amount of material used is selected as the cost driver. As the demand quantity of the product is increase by 10%, the total cost of production is predicted to be MYR 4,260,115.20 while the unit product cost is forecast at MYR 0.81. Through TDABC method, this work gains information on practical capacity of operator which is 123,600 minutes. Moreover, the capacity cost rate for winding activity is MYR 2.53 and the time equation is 0.12χ1 with χ 1 as variable of amount of raw material of 8,697.6 kilograms. All sub-activities are analyzed and categorized in 3 categories which are optimistic, most likely and pessimistic. There are 7 sub-activities under optimistic category, 6 sub-activities under most likely and 4 subactivities under pessimistic. In conclusion, by implementing and comparing of ABC and TDABC at the company, this work proves TDABC is a method with objective cost driver determination, removes time consuming process, have multiple cost drivers and able to forecast and planning using analysis of capacity utilization. Thus, TDABC can improve the company costing structure by using the advantages of TDABC in order to gain detailed decision-making process.